Strategi Guru PAI untuk Meningkatkan Kemampuan Membaca dan Menulis Al-Qur’an di Kelas VII SMP Wachid Hasjim 9 Sedati Sidoarjo - Fadhila, Ririn Nur; Masnawati, Eli (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
This research aims to identify and analyze the strategies implemented by Islamic Education (PAI) teachers to enhance the Quranic reading and writing skills of seventh-grade students at SMP Wachid Hasjim 9 Sedati Sidoarjo. The case study method is combined with a qualitative approach in this study. Through in-depth interviews, direct observation, and relevant documentation, data were gathered. The aftereffects of the review show that the technique cycle in further developing perusing and composing the Qur'an includes the job of PAI Teachers. The strategies include routine activities for 30 minutes before lessons begin, which encompass reading the Quran using the Qur’an Kemenag smartphone application and writing using the Imlak method, as well as efforts to motivate students. The challenges encountered include a limited number of PAI teachers, insufficient WIFI facilities, and diversity in students' abilities, intelligence, interests, backgrounds, and discipline. To overcome these challenges, consistent and ongoing efforts from the school are necessary, including the implementation of policies to discipline students who do not comply with or perform Quranic reading and writing activities properly. The findings of this study align with and support relevant theories and previous research on the development of Quranic literacy skills in schools